2017
DOI: 10.1136/bmjgh-2017-000327
|View full text |Cite
|
Sign up to set email alerts
|

Leaving no one behind: lessons on rebuilding health systems in conflict- and crisis-affected states

Abstract: Conflict and fragility are increasing in many areas of the world. This context has been referred to as the ‘new normal’ and affects a billion people. Fragile and conflict-affected states have the worst health indicators and the weakest health systems. This presents a major challenge to achieving universal health coverage. The evidence base for strengthening health systems in these contexts is very weak and hampered by limited research capacity, challenges relating to insecurity and apparent low prioritisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 28 publications
2
82
0
Order By: Relevance
“…This was accomplished by positively in uencing national policies and guidance, strengthening local coordination mechanisms, capacitating the healthcare workforce with competency-based training, mentoring, on-the-job training, and supportive supervision (bene ting facilities supported by the project and beyond), developing the capacity of project and MoH staff in the effective management of the supply chain, actively and creatively mobilizing the community to raise awareness and create demand, and providing quality and affordable services. Contributions of this package to increased utilization of services and long-acting contraceptives were quantitatively evidenced in previous publications[12][13][14].Save the Children's strategic and programmatic investments align with the results of a study published in 2017 by Martineau et al who analyzed research evidence on rebuilding health systems in con ict-and crisis-affected countries[25]. According to the analysis, the starting points for policy development and systems strengthening are the community, human resources for health, and institutions.With regard to institutions, the arrival of multiple actors and resulting power dynamics requires strong coordination to optimize the capacity building and response of national and local institutions[26].…”
mentioning
confidence: 54%
“…This was accomplished by positively in uencing national policies and guidance, strengthening local coordination mechanisms, capacitating the healthcare workforce with competency-based training, mentoring, on-the-job training, and supportive supervision (bene ting facilities supported by the project and beyond), developing the capacity of project and MoH staff in the effective management of the supply chain, actively and creatively mobilizing the community to raise awareness and create demand, and providing quality and affordable services. Contributions of this package to increased utilization of services and long-acting contraceptives were quantitatively evidenced in previous publications[12][13][14].Save the Children's strategic and programmatic investments align with the results of a study published in 2017 by Martineau et al who analyzed research evidence on rebuilding health systems in con ict-and crisis-affected countries[25]. According to the analysis, the starting points for policy development and systems strengthening are the community, human resources for health, and institutions.With regard to institutions, the arrival of multiple actors and resulting power dynamics requires strong coordination to optimize the capacity building and response of national and local institutions[26].…”
mentioning
confidence: 54%
“…The current study will serve (1) research and health institutions interested in global health security to better assess research on fragile states [14]; (2) international health agencies to allocate research gaps in these fragile states and tailor health support and health aids based on the identified gaps; (3) international funding agencies to strengthen health systems in most neglected health aspects [15,16]; and (4) create and encourage research collaboration with colleagues in fragile states to rebuild the health research capabilities [17].…”
Section: Resultsmentioning
confidence: 99%
“…Health systems in humanitarian settings are often poorly resourced and suffer from workforce shortages. 4 Controlling COVID-19 requires multidisciplinary input from doctors to cleaners, whose integral role in prevention of spread of disease is often disregarded. 5 A 2015 survey on infection prevention and control (IPC) preparedness of institutions worldwide showed that preparedness levels were only partially adequate.…”
Section: Summary Boxmentioning
confidence: 99%